The effect of two different parenteral nutrition regimens on parenteral nutrition-associated cholestasis. (May 2013) - Özlü, Ferda; Yapıcıoğlu, Prof Hacer; Mer, Kurthan; Satar, Mehmet; Narlı, Nejat; Sertdemir, Yaşar
Abstract Exposure to parenteral nutrition (PN) is one major factor in the development of cholestasis. The aim of this retrospective study was to compare the effect of these two different PN regimens on PN-associated cholestasis (PNAC). The files of the patients who have received different PN regimens for >14 d in 2005 and 2009 were retrospectively reviewed. 133 patients have received PN more than 14 d. 22 (16.5%) patients had PNAC. 90 neonates were in Group low-dose parenteral (LDpn) and 43 neonates in Group high-dose parenteral. Mean gestational age and birth weight were statistically significantly lower in LDpn Group (p = 0.016, p = 0.434). Cholestasis rate was significantly higher in high dose group. (p = 0.023). Although several risk factors for PNAC are unavoidable, research is still needed to define the optimal parenteral amino acid solution for neonatal patients. Individualized PN may be more affective in allowing growth and minimizing side effects.